Literature Review: Hubungan Perilaku Merokok dengan Penyakit Jantung Koroner - Anggraeni, Dea Lutfi; Enrica, Keisha Mutiara; Khairunnisa, Naurah Sa’adah; Aropah, Patimah Nurul; Raharjo, Rezeki; Roidah, Syifa Adzkia Nur; Sopiah, Popi (Pustaka Galeri Mandiri, 2025)
Coronary heart disease is a heart disease caused by the buildup of cholesterol (plaque), fat, or other substances on the walls of blood vessels. Plaque buildup can narrow the arteries and reduce blood flow that carries oxygen and nutrients to the heart. Coronary Heart Disease (CHD) remains one of the leading causes of death in the world and in Indonesia. One of the most influential lifestyle risk factors for the emergence of CHD is smoking. Harmful substances in cigarettes such as nicotine and carbon monoxide can damage the endothelium of blood vessels, thereby increasing the risk of cardiovascular disorders. This study aims to analyze the level of risk of coronary heart disease in individuals who smoke compared to individuals who do not smoke through a literature review. This study used the Narrative Literature Review method with reference to the PRISMA guidelines. Article searches were conducted through the Google Scholar database with a publication range of 2020–2025. Based on the results of the literature review, a significant relationship was found between smoking behavior and the incidence of CHD. Individual smokers have a risk (Odds Ratio) between 1.75 to 5.9 times greater for developing CHD compared to non-smokers. This risk increases with the intensity and duration of smoking, and also impacts passive smokers. The chemicals in cigarettes have been shown to accelerate atherosclerosis and narrowing of the arteries. Smoking is a dominant modifiable risk factor. Quitting smoking can significantly reduce the risk of coronary heart disease. Health promotion and education efforts regarding the dangers of smoking need to be increased.